Symbolic Meaning Analysis in the Arabic Lyrics of the Song Dreamers: A Riffaterre Semiotics Study - Nursukma Suri; Sintya Maharani; Nadia Fadila; Masito Hasibuan (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2026)
This study aims to uncover the symbolic meanings and hidden messages in the Arabic lyrics of the song “Dreamers,” performed by Jungkook and Fahad Al-Kubaisi. Using a qualitative descriptive method and Riffaterre’s semiotic approach, the analysis focuses on the discontinuity of expression, heuristic-hermeneutic readings, as well as matrices, models, and hypograms. This study concludes that the meaning of the lyrics is not merely entertainment, but a medium of symbolic expression regarding hope, solidarity, and a universal spirit. The results of this study indicate that: (1) a heuristic reading of the “Dreamers” lyrics depicts a story of individuals who dream and strive to realize those dreams; (2) a hermeneutic reading reveals deeper meanings regarding spirit, optimism, and the conviction to achieve future hopes; (3) the matrix of this song centers on the ideas of dreams and hope; (4) the emerging model is the figure of “dreamers” who dare to dream and continue to strive to achieve their goals; and (5) the hypogram of this song relates to the discourse of motivation, hard work, and the spirit of unity that frequently appears in modern inspirational texts.